2010
DOI: 10.1007/s00240-010-0320-3
|View full text |Cite
|
Sign up to set email alerts
|

Composition and morphology of phosphate stones and their relation with etiology

Abstract: Calcium phosphate (CaP) stones account for about 15% of all urinary stones, with a marked female preponderance, and reflect a wide diversity of etiology. Variation of the relative prevalence of CaP urolithiasis over time is disputed, and relevance of CaP stone analysis for etiologic diagnosis is underestimated or even negated. Based on the analysis of more than 50,000 stones over the past three decades, we evaluated the changes in the relative proportion of CaP stones between 1980-1989 (period 1) and 2000-2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 43 publications
9
67
0
4
Order By: Relevance
“…Our findings are in good agreement with previous results [9], which showed that the formation of group I calculi is associated with renal tubular acidosis, whereas the formation of group II calculi is associated with hypercalciuria and low urinary pH. In addition, we also showed that high urinary phosphate concentration is a characteristic of group II calculi, with all of these samples containing some amount of COM and COD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in good agreement with previous results [9], which showed that the formation of group I calculi is associated with renal tubular acidosis, whereas the formation of group II calculi is associated with hypercalciuria and low urinary pH. In addition, we also showed that high urinary phosphate concentration is a characteristic of group II calculi, with all of these samples containing some amount of COM and COD.…”
Section: Discussionsupporting
confidence: 93%
“…Elevated urinary pH may be associated in some patients with renal tubular acidosis [8], but usually occurs in women without any clinical alterations [7]. Recently a large study of all types of calcium phosphate calculi, including those associated with urinary tract infection that also contain struvite, showed that hypercalciuria was present in 87% of patients with brushite-containing calculi and in 60% of those with hydroxyapatite stones, whereas renal tubular acidosis was associated with hydroxyapatite stones showing a peculiar morphology [9]. That study, however, did not fully assess the characteristics of stones in patients with high urinary phosphate concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…While the presence of carboapatite could denote the metabolic origin of the stone followed by a super infection causing struvite precipitation [18], an entire infectious origin cannot be discarded. A more in-depth analysis with the determination of the carbonation rate of carboapatite in these stones would support this role [19].…”
Section: Discussionmentioning
confidence: 81%
“…The information provided by the present study may aid in selecting a more appropriate prophylaxis for patients with urolithiasis. CaP stones account for ~15% of all urinary stones, with a marked female preponderance, and reflect a wide diversity of etiologies (31). CA.AP is the most frequent crystalline phase (74.0%) of CaP and stones composed thereof have a number of possible causes, including metabolic disorder (such as hypercalciuria, hypocitraturia, tubular acidosis, primary hyperparathyroidism and medullary sponge kidney) and chronic urinary tract infection, while the latter etiology remains under debate.…”
Section: Discussionmentioning
confidence: 99%